Green Synthesis of 5‐Hydroxymethylfurfural from Chitosan Biomass Catalyzed by Benzimidazole‐Based Ionic Liquids. Issue 32 (13th November 2017) - Zhang, Mingchuan; Zang, Hongjun; Ma, Bin; Zhang, Xiaolei; Xie, Ruirui; Cheng, Bowen
Abstract: 5‐Hydroxymethylfurfural (5‐HMF) is one of the most important platform chemicals in biorefinery, which could be further converted into bio‐fuels. In this work, an effective and green route for 5‐HMF production from chitosan biomass in a dimethylsulfoxide (DMSO)/water mixed solvent using acidic ionic liquids as the catalysts is reported. Several ionic liquids were successfully synthesized and used as catalysts for the degradation of chitosan. Benzimidazolium chloride ([Hbim]Cl) exhibited the best catalytic activity. We achieved a maximum 5‐HMF yield of 34.9 mol% in 10 wt% DMSO‐water mixed solvent. Moreover, the catalyst could be easily recycled and reused at least five times without a significant loss of activity. Our investigation involved the use of recycled catalysts and crustacean waste as the starting material, which makes the process "green" and sustainable. Abstract : Easily synthesized benzimidazole‐based ionic liquids were used as catalysts for the conversion of chitosan biomass to value‐added platform chemical 5‐HMF under mild hydrothermal conditions. [Hbim]Cl showed high catalytic activity in pure water. Meanwhile, it can be recycled easily and reused several times without significant loss of activity.